Village Government Governance In Determining Border Tapes Between Buluh Manis Village And Pematang Pudu Village In Bengkalis District - Ahmad Fitra Yuza; Jumiyanti Syafitri (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2021)
This research examines the Governance of Village Governments in Determining Boundaries which have problems regarding Governance in the settlement of boundaries. This study aims to determine village government governance in determining the boundaries between Buluh Manis Village and Pematang Pudu Village in Bengkalis Regency. This type of research, which is located in Buluh Manis Village, Bathin Solapan District and Pematang Pudu Village in Mandau District, is descriptive with qualitative methods, namely research that seeks to describe the object or subject under study in accordance with what it is, and to explain variables and indicators. The results of the study regarding Village Government Governance in Determining the Boundary between Buluh Manis Village and Pematang Pudu Village in Bengkalis Regency were analyzed through four indicators. First, the accountability is both normative accountability and positive accountability can be correlated well because the Bengkalis Regency Government in solving this problem is responsible for the authority assigned to it as it has done several stages of solving the boundary problem between Buluh Manis Village and Pematang Pudu Village . Second, the transparency, namely the openness of the process in the formulation of public policies and the action of its implementation can be seen by the community knowing how the process in the formulation of decision-making to determine the boundaries between Buluh Manis Village and Pematang Pudu Village or in the implementation action which also includes representatives from the community such as community leaders. Third, the participation is that the Bengkalis Regency Government has conducted mediation by opening a discussion forum between the parties involved in the completion of boundary determination. Fourth, the legal certainty that there is no legal certainty or applicable regulations set by the Bengkalis Regency Government in resolving the boundary problems between Buluh Manis Village and Pematang Pudu Village.